Screening Wheat Genotypes for Growth and Yield-Related Traits Under Normal and Salt Stress Conditions - Kausar, Rizwana; Abbas, Syed Karamat; Munsha, Asma; Khan, Aftab Ahmad; Shah, Syed Asghar Hussain; Noor, Sobia; Pervez, Asim; Rabnawaz; Ghafoor, Shamsa; Aslam, Tanzila; Ahmad, Muhammad Ibrar (Journal of Agriculture and Biology, 2025)
Salinity stress is a major abiotic factor limiting wheat (Triticum aestivum L.) growth and productivity worldwide.  A pot experiment was conducted at the Department of Plant Breeding and Genetics, University of Agriculture, Faisalabad, using a completely randomized design (CRD) with three replications. The wheat genotypes were evaluated under normal and saline (8 dSm-1) conditions for key agronomic traits. Analysis of variance (ANOVA) revealed significant variations among genotypes, treatments, and their interactions, indicating that salinity stress significantly influenced all measured traits. Principal Component Analysis (PCA) identified plant height, peduncle length, flag leaf area, and grain yield per plant as the most influential traits under stress conditions. Among the tested genotypes, Markaz-19, Ghazi-19, and Subhani-21 demonstrated superior performance under salinity stress, suggesting their potential as salt-tolerant candidates for future breeding programs.
Keywords: Salinity stress; wheat; CRD; PCA; tolerance